Characterization of Nodulation-Compatible Strains of Native Soil Rhizobia from the Rhizosphere of Soya Bean (Glycine max L.) Fields in South Africa - Khumbudzo Ndhlovu; Francina Lebogang Bopape; Mamonokane Olga Diale; Tiisetso Mpai; Liesl Morey; Nompumelelo Prudence Mtsweni; Abe Shegro Gerrano; Ansa van Vuuren; Olubukola Oluranti Babalola; Ahmed Idris Hassen (Nitrogen)
Prolonged inoculation of soya bean (Glycine max L.) farms with exotic strains of Bradyrhizobium species starting in the 1960s resulted in the establishment of populations of Bradyrhizobium strains in the soils of several soya bean farms in South Africa. With the increasing number of new soya bean genotypes in the country, it is challenging to determine which genotypes are highly compatible with a given rhizobium strain. In this study, we investigated the symbiotic compatibility of native rhizobial isolates and the strains from the South African Rhizobium Culture Collection (SARCC) on ten selected locally available soya bean genotypes. A glasshouse soil trap experiment using soil samples collected from Lothair, Bothaville, and Standerton was performed on five cultivars. The trapped rhizobial strains were further screened in the glasshouse to authenticate their nodulation compatibility with the different soya bean cultivars. The rhizobial strains showed significant nodulation compatibility with the selected cultivars. These strains were also tested for beneficial traits in vitro and characterized using DNA sequencing methods to elucidate their taxonomic identity. Some of the most nodulation-compatible strains characterized as Bradyrhizobium and Sinorhizobium species exhibited significant symbiotic performance in terms of plant biomass, nodule number, and nodule dry weight. The study generated valuable data that provide information on the extent of symbiotic compatibility of some of the existing cultivars used in South Africa with native rhizobia and whether inoculation of soya bean with commercial products is vital on some soya bean farms.